STI policy and management journal - Pusat Penelitian Perkembangan Iptek (Indonesia) (published by the Center for Science and Technology Development Studies at the Indonesian Institute of Sciences (Pappiptek-LIPI), 2016)
Scientific journal discussing theoretical and practical issues in science and technology policy for economic competitiveness, research and development management and innovation management.
Keywords: Technology : Indonesia : Management : Periodicals; Technology : Periodicals; Technological innovations : Indonesia : Management : Periodicals; Technological innovations : Periodicals; Technological innovations; Technological innovations : Management; Technology; Technology : Management; Indonesia